Conditioned spin and charge dynamics of a single-electron quantum dot - Greplova, E; Laird, E; Briggs, G; Mølmer, K (American Physical Society, 2017)
In this article we describe the incoherent and coherent spin and charge dynamics of a single-electron quantum dot. We use a stochastic master equation to model the state of the system, as inferred by an observer with access to only the current signal through a quantum point contact, acting as a charge sensor. Measurements obtained during an interval of time contribute, by a past quantum state analysis, to our knowledge about the system at any time t within that interval. Such analysis permits precise estimation of physical parameters and we propose and test a modification of the classical Baum-Welch parameter reestimation method to systems driven by both coherent and incoherent processes.